The Effect Of Sector Credit Concentration Risks On Bank Profitability And Risks An Applied Study On Private Islamic Banks In Syria - Al-Mamlouk, Anas Hisham (Latakia University Journal - Economic and Legal Sciences Series, 2020)
Concentration risk is one of the main reasons that may result in losses that greatly affect the bank, which may threaten the bank’s continuity in its business. Achieving a balance between concentration and diversification in the credit portfolio is a very important matter for banks, except that diversifying the credit portfolio requires expertise In different and multiple areas that may not be available to all of the banks in most cases, in addition to the costs of diversification that negatively affect the returns of the credit facilities granted, especially since these returns constitute the most important source of profit for banks, which makes banks tend To focus on its credit portfolios, with the aim of achieving more profits and then achieving better performance, It should be noted that concentration risks were not fully addressed within the first pillar of Basel II decisions, and accordingly, banks should be aware that concentration risks can arise in items both inside and outside the budget in their credit portfolios, Based on the foregoing, the aim of this research is to find out the effect of the concentration of the credit portfolio of banks on the level of the economic sector, where the researcher applied his study to private Islamic banks in Syria listed on the Damascus Stock Exchange where the data of these banks were studied during the period from the beginning of the first year 2011 to the end of 2018 by relying on the Herfindahl-Hirschman - HHI index to measure the concentration of the credit portfolio, The study concluded that there is a direct relationship between the degree of sectoral credit concentration in the credit facilities portfolio and the degree of risk to which the research sample banks are exposed, as well as the absence of a relationship between the degree of sectoral credit concentration in the credit facilities portfolio and the profitability of the portfolio in addition to a direct relationship between the degree of sectoral concentration and performance Research sample banks. تعتبر مخاطر التركز أحد الأسباب الرئيسية التي قد ينتج عنها خسائر مؤثرة بشكل كبير على البنك مما قد يهدد استمرار البنك في مزاولة أعماله ، و يعد تحقيق التوازن بين التركز والتنويع في المحفظة الائتمانية أمرًا مهمًا جدًا الأهمية بالنسبة إلى المصارف، إلاَّ أن تنويع المحفظة الائتمانية يتطلب خبراتٍ في مجالاتٍ مختلفةٍ ومتعددةٍ قد لا تتوافر لدى المصارف كّلها في أغلب الأحيان، فضلا عن تكاليف التنويع التي تؤثر سلبًا في عوائد التسهيلات الائتمانية الممنوحة، ولاسيما أن هذه العوائد تشكل مصدر الربح الأكثر أهمية بالنسبة إلى المصارف الأمر الذي يجعل المصارف تميل إلى التركز في محافظها الائتمانية، وذلك بهدف تحقيق مزيدٍ من الأرباح ومن ثم تحقيق أداء أفضل. وتجدر الإشارة إلى أن مخاطر التركز لم يتم تناولها كلية ضمن الدعامة الأولى في إطار مقررات بازل 2، وبناء على ذلك فإنه يتعين على البنوك أن تكون على دراية بأن مخاطر التركز يمكن أن تنشأ في البنود داخل وخارج الميزانية في محافظها الائتمانية. وبناء على ما سبق هدف هذا البحث الى معرفة أثر تركز المحفظة الائتمانية للمصارف في مستوى القطاع الاقتصادي، حيث طبق الباحث دراسته على المصارف الإسلامية الخاصة في سورية المدرجة في سوق دمشق للأوراق المالية حيث درِستْ بيانات هذه المصارف خلال المدة الممتدة من بداية الأول العام 2011 إلى نهاية عام 2018 من خلال الاعتماد على مؤشر Herfindahl-Hirschman - HHI لقياس تركز المحفظة الائتمانية وخلصت الدراسة إلى وجود علاقة طردية بين درجة التركز الائتماني القطاعي في محفظة التسهيلات الائتمانية و ودرجة المخاطر التي تتعرض لها المصارف عينة البحث فضلاً عن عدم وجود علاقة بين درجة التركز الائتماني القطاعي في محفظة التسهيلات الائتمانية وربحية المحفظة إضافة إلى وجود علاقة طردية بين درجة التركز القطاعي وأداء المصارف عينة البحث.